Bioprocessing of Crop Residues using Fibrolytic Enzymes and Flavobacterium bolustinum for Enriching Animal Feed - Malik, Suman; Sharma, Sampriya; Sharma, Jitender; Mandhan, Rishi Pal (International Journal of Biotechnology for Wellness Industries, 2015)
Flavobacterium bolustinum and its extracellular cellulase were tested for animal feed pretreatment. The fibrolytic enzymes, cellulase and pectinase were applied to various crop residues such as wheat straw, rice straw, corn seeds and sorghum for enriching animal feed. Different parameters like temperature, incubation time and enzyme dose had been optimized for maximum reducing sugar and protein release. The highest amount of reducing sugar obtained was 29.83 mg g-1 dry substrate and soluble protein was 27.34 mg g-1 dry substrate on single cellulase enzyme treatment at 50°C for 6 h. An increase in amount of released reducing sugar (39.5 mg g-1 dry substrate) and protein (33.88 mg g-1 dry substrate) was observed when enzyme cocktail (cellulose and pectinase) was used. Solid state fermentation using F. bolustinum had also been performed for all crop residues. It released higher amount of reducing sugar (41.36 mg g-1) and protein (47.21 mg g-1) as compared to enzymatic treatment. Different substrates resulted in appreciable weight loss by enzymatic treatment (15-35%) as well as fermentation using F. bolustinum (40%). Liquefaction of lignocellulosic rich crop residues, for better utilization of feed has never been reported earlier.